Light Activates the Translational Regulatory Kinase GCN2 via Reactive Oxygen Species Emanating from the Chloroplast - Lokdarshi, Ansul; Guan, Ju; Urquidi Camacho, Ricardo A.; Cho, Sung Ki; Morgan, Philip W.; Leonard, Madison; Shimono, Masaki; Day, Brad; von Arnim, Albrecht G. (The Plant cell, 2020)
Cytosolic mRNA translation is subject to global and mRNA-specific controls. Phosphorylation of the translation initiation factor eIF2α anchors a reversible regulatory switch that represses cytosolic translation globally. The stress-responsive GCN2 kinase is the only known kinase for eIF2α serine 56 in Arabidopsis ( ). Here, we show that conditions that generate reactive oxygen species (ROS) in the chloroplast, including dark-light transitions, high light, and the herbicide methyl viologen, rapidly activated GCN2 kinase, whereas mitochondrial and endoplasmic reticulum stress did not. GCN2 activation was light dependent and mitigated by photosynthesis inhibitors and ROS quenchers. Accordingly, the seedling growth of multiple Arabidopsis mutants was retarded under excess light conditions, implicating the GCN2-eIF2α pathway in responses to light and associated ROS. Once activated, GCN2 kinase preferentially suppressed the ribosome loading of mRNAs for functions such as mitochondrial ATP synthesis, the chloroplast thylakoids, vesicle trafficking, and translation. The mutant overaccumulated transcripts functionally related to abiotic stress, including oxidative stress, as well as innate immune responses. Accordingly, displayed defects in immune priming by the fungal elicitor, chitin. Therefore, we provide evidence that reactive oxygen species produced by the photosynthetic apparatus help activate the highly conserved GCN2 kinase, leading to eIF2α phosphorylation and thus affecting the status of the cytosolic protein synthesis apparatus.